Marine antifouling and anticorrosive coating and its spraying process
Patent Information
- Application Number
- CN202110779836.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-07-09
AI Technical Summary
[0024]The beneficial effects of this invention are as follows: A robust anti-corrosion coating is formed on the steel or aluminum substrate of the ship using high-power supersonic electric arc spraying of Zn-Al metal-ceramic alloy wire or aluminum-zinc coated composite powder core wire. Then, a low-surface-energy coating with good compatibility and compatibility is applied to the uniquely rough surface of the layered structure of the sprayed coating. This results in a coating structure with high bonding strength, integrated corrosion resistance, fouling resistance, and erosion resistance. The coating material is easily industrially prepared, and the pretreatment and composite coating preparation technologies are well-matched, enabling remanufacturing and rapid repair on the slipway and on-site.
Smart Images

Figure CN113717563B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-corrosion material preparation technology, and in particular to a marine antifouling and anti-corrosion coating and its spraying process. Background Technology
[0002] The deposition process of marine organisms on equipment surfaces can generally be divided into four stages: After the substrate is immersed in seawater for several minutes, a regulating film forms on the surface, providing nutrients for microbial growth and reproduction. Within hours, bacteria and algae deposited on the regulating film secrete extracellular polymers to form a bacterial biofilm. Within a few days, bacteria and algae rapidly grow into spores or protozoa. Within a few months, spores and protozoa grow into large depositional organisms such as algae. Based on the deposition process and influencing factors of marine organisms, marine antifouling materials can be broadly classified into biocidal, self-dispelling, anti-deposition, and deposition-releasing coatings.
[0003] The waterline area and underwater sections of ships are the most susceptible and severely affected by corrosion, which mainly includes chemical corrosion, electrochemical corrosion, cavitation corrosion, and marine biological corrosion. There are many methods to protect ships from corrosion, such as selecting corrosion-resistant materials, coating protection, sacrificial anode protection, and external power supply protection. Among these, coating protection is one of the most important measures for protecting hull materials.
[0004] The following describes a coating and spraying process for metal parts based on coating protection. This process is convenient to apply, easy to maintain, and simple to operate. The combined effect of mechanical bonding, chemical bonding, and physical entanglement effectively improves the coating effect and the overall structural strength, meeting the practical needs of ships. Summary of the Invention
[0005] Therefore, the purpose of this invention is to provide a novel hull coating structure and spraying process to help improve the antifouling and corrosion resistance of existing ship structural components.
[0006] The present invention achieves the above objectives through the following technical solution: a marine antifouling and anticorrosion coating comprising a metal-ceramic base layer, an SEBS structural layer, and a PS-b-PDMS-r-PVMS / MNPs@Laf active layer;
[0007] Metal-ceramic base layer: The metal-ceramic base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate, Zn-Al alloy as the main component, and TiO2, SiO2 and rare earth oxides as auxiliary components, and is sprayed onto the substrate to obtain the metal-ceramic base layer.
[0008] SEBS structural layer: A macromolecular coupling agent is coated on the surface of the metal-ceramic base layer. The -OH group on the surface of the metal-ceramic base layer is organically combined with the silanol group at one end of the macromolecular coupling agent. The epoxy group and amino group at the other end of the macromolecular coupling agent are bonded to the maleic anhydride-modified SEBS in the metal-ceramic base layer to obtain the SEBS structural layer.
[0009] PS-b-PDMS-r-PVMS / MNPs@Laf active layer: A composite material made of PS-b-PDMS-r-PVMS block polymer as matrix and ~100nm monodisperse MNPs@Laf nanospheres as additives. The block polymer PS-b-PDMS-r-PVMS is dissolved in ethyl acetate and uniformly mixed with FeCo / gelatin nanospheres adsorbed with small molecules. The mixture is then coated on the SEBS structural layer to obtain the PS-b-PDMS-r-PVMS / MNPs@Laf active layer.
[0010] An antifouling and anticorrosion coating is obtained by setting the SEBS structural layer on the metal-ceramic base layer and setting the PS-b-PDMS-r-PVMS / MNPs@Laf active layer on the basis of the SEBS structural layer.
[0011] A spraying process for a marine antifouling and anticorrosion coating;
[0012] Step 1: Based on the substrate, the substrate is cleaned and sandblasted; the surface cleanliness after treatment reaches Sa3 and the roughness reaches Rz25−100μm;
[0013] The sandblasting process parameters are as follows:
[0014] Cast iron sand is selected as the abrasive, with a particle size of 0.5mm to 1.5mm. The abrasive must be angular, clean, dry, and free of oil.
[0015] All compressed air undergoes a cooling device and an oil-water separator during the injection process to ensure that the compressed air is dry, oil-free, and at a pressure of 0.7 MPa.
[0016] Maintain a distance of 100mm to 300mm between the nozzle and the base metal surface;
[0017] The angle between the spraying direction and the normal to the base metal surface is controlled within the range of 15 to 30°.
[0018] After surface pretreatment, remove dust and debris with dry, oil-free compressed air. Do not touch the cleaned surface with your hands.
[0019] Step 2: Plasma spray Zn-Al alloy onto the substrate surface after Step 1, and then plasma spray Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials in a ratio of 2:3:2:1:2 onto the metal layer to obtain a substrate with a metal-ceramic base layer.
[0020] Step 3: Using ethyl acetate as a solvent, prepare a mixed solution of SEBS (hydrogenated styrene-butadiene block copolymer), MA-SEBS (maleic anhydride-modified SEBS), and macromolecular coupling agent (C8H22O3N2Si) with a concentration ratio of 1:1:2. Then, use a booster pump to increase the pressure of the coating to 160-280 kg / cm² on the substrate surface treated in Step 2. 2 Spraying 50μm, the silanol groups on the macromolecular coupling agent organically combine with the -OH on the surface of the metal-ceramic base layer, and the epoxy groups and amino groups bond with the maleic anhydride-modified SEBS in the metal-ceramic base layer, so that SEBS grows on the surface of the metal-ceramic material and the SEBS structure layer is obtained.
[0021] Step 4: Prepare an ethyl acetate solution containing the block polymer PS-b-PDMS-r-PVMS with a concentration of 10 mol / L. Mix the prepared ethyl acetate solution with FeCo / gelatin nanospheres that have adsorbed small molecules, and then coat the substrate surface treated in Step 3 with a thickness of 30 μm to complete the overall coating.
[0022] Furthermore, the metal-ceramic base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate. The substrate is cleaned and sandblasted. Zn-Ni alloy is used as the metal layer material, and Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides are used as ceramic layer raw materials. The metal layer material is arc-sprayed onto the surface of the substrate, and then the ceramic layer raw materials are arc-sprayed to obtain a double-layer base layer of metal and ceramic.
[0023] Furthermore, the Zn-Ni balance is 20%–35%, and the mass ratio of Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides is 2:3:2:1:2.
[0024] The beneficial effects of this invention are as follows: A robust anti-corrosion coating is formed on the steel or aluminum substrate of the ship using high-power supersonic electric arc spraying of Zn-Al metal-ceramic alloy wire or aluminum-zinc coated composite powder core wire. Then, a low-surface-energy coating with good compatibility and compatibility is applied to the uniquely rough surface of the layered structure of the sprayed coating. This results in a coating structure with high bonding strength, integrated corrosion resistance, fouling resistance, and erosion resistance. The coating material is easily industrially prepared, and the pretreatment and composite coating preparation technologies are well-matched, enabling remanufacturing and rapid repair on the slipway and on-site. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the coating structure;
[0026] Figure 2 It is the cross section of the basic coating;
[0027] Figure 3 It is the coating section; Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In the description of this invention, it should be understood that the terms "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0030] Combination Figures 1-3 The technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0031] Example 1:
[0032] This invention provides a marine antifouling and corrosion-resistant coating, comprising a metal-ceramic base layer, an SEBS structural layer, and a PS-b-PDMS-r-PVMS / MNPs@Laf active layer. The process involves conventionally cleaning and sandblasting the ship's metal plates, then spraying the metal-ceramic material onto the metal substrate surface. A macromolecular modifier is used to further modify the sprayed metal-ceramic material, enabling it to chemically bond with SiO2, TiO2, etc., within the metal-ceramic material, and to combine with anhydride-modified SEBS, allowing SEBS to grow on the metal-ceramic material surface. Finally, through segment entanglement and concentration diffusion, the PS-b-PDMS-r-PVMS / MNPs@Laf active layer is constructed on the coating surface.
[0033] Metal-ceramic base layer: The base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate, with Zn-Al alloy as the main component and TiO2, SiO2 and rare earth oxides as auxiliary components, and is sprayed onto the substrate to obtain the metal-ceramic base layer.
[0034] SEBS structural layer: A macromolecular coupling agent is coated on the surface of the base layer. The -OH group on the surface of the metal-ceramic base layer is organically combined with the silanol group at one end of the macromolecular coupling agent. The epoxy group and amino group at the other end of the macromolecular coupling agent are bonded to the maleic anhydride-modified SEBS in the metal-ceramic base layer to obtain the SEBS structural layer.
[0035] PS-b-PDMS-r-PVMS / MNPs@Laf active layer: A composite material made of PS-b-PDMS-r-PVMS block polymer as matrix and ~100nm monodisperse MNPs@Laf nanospheres as additives. The block polymer PS-b-PDMS-r-PVMS is dissolved in ethyl acetate and uniformly mixed with FeCo / gelatin nanospheres adsorbed with small molecules. The mixture is then coated on the structural layer to obtain the PS-b-PDMS-r-PVMS / MNPs@Laf active layer.
[0036] An antifouling and anti-corrosion coating is obtained by setting a structural layer on a base layer and then setting an active layer on top of the structural layer.
[0037] A spraying process for a marine antifouling and anticorrosion coating:
[0038] Step 1: Based on the substrate, the substrate is cleaned and sandblasted; the surface cleanliness after treatment reaches Sa3 and the roughness reaches Rz25−100μm.
[0039] Sandblasting process parameters
[0040] Cast iron sand is selected as the abrasive, with a particle size of 0.5mm to 1.5mm. The abrasive must be angular, clean, dry, and free of oil.
[0041] All compressed air undergoes a cooling device and an oil-water separator during the injection process to ensure that the compressed air is dry, oil-free, and at a pressure of 0.7 MPa.
[0042] Maintain a distance of 100mm to 300mm between the nozzle and the base metal surface;
[0043] The angle between the spraying direction and the normal to the base metal surface is controlled within the range of 15 to 30°.
[0044] After surface pretreatment, remove dust and debris with dry, oil-free compressed air. Do not touch the cleaned surface with your hands.
[0045] Step 2: Plasma spray Zn-Al alloy onto the substrate surface after Step 1, and then plasma spray Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials in a ratio of 2:3:2:1:2 onto the metal layer to obtain a substrate with a metal-ceramic base layer.
[0046] Step 3: Using ethyl acetate as a solvent, prepare a mixed solution of SEBS (hydrogenated styrene-butadiene block copolymer), MA-SEBS (maleic anhydride-modified SEBS), and macromolecular coupling agent (C8H22O3N2Si) with a concentration ratio of 1:1:2. Then, use a booster pump to increase the pressure of the coating to 160-280 kg / cm² on the substrate surface treated in Step 2. 2 ) Spraying 50μm, the silanol groups on the macromolecular coupling agent organically combine with the -OH on the surface of the metal-ceramic base layer, and the epoxy groups and amino groups bond with the maleic anhydride-modified SEBS in the metal-ceramic base layer, so that SEBS grows on the surface of the metal-ceramic material and obtains the SEBS structure layer.
[0047] Step 4: Prepare an ethyl acetate solution containing the block polymer PS-b-PDMS-r-PVMS with a concentration of 10 mol / L. Mix the prepared ethyl acetate solution with FeCo / gelatin nanospheres that have adsorbed small molecules, and then coat the substrate surface treated in Step 3 with a thickness of 30 μm to complete the overall coating.
[0048] The specific spraying parameters are as follows: metal layer spraying parameters: working current 400, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.15L / min, alloy powder feeding rate 80g / min, and spraying thickness 150μm;
[0049] Ceramic layer spraying parameters: operating current 500, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.25L / min, alloy powder feeding rate 75g / min, spraying thickness 120μm.
[0050] The metal-ceramic base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate. The substrate is cleaned and sandblasted. Zn-Ni alloy is used as the metal layer material, and Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides are used as ceramic layer raw materials. The metal layer material is arc-sprayed onto the substrate surface and then the ceramic layer raw materials are arc-sprayed to obtain a double base layer of metal and ceramic layers.
[0051] The Zn-Ni balance is 20%–35%, and the mass ratio of Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides is 2:3:2:1:2.
[0052] Example 2:
[0053] A spraying process for a marine antifouling and anticorrosion coating:
[0054] Step 1: Based on the substrate, the substrate is cleaned and sandblasted; the surface cleanliness after treatment reaches Sa3 and the roughness reaches Rz25−100μm.
[0055] Sandblasting process parameters
[0056] Cast iron sand with a particle size of 0.5mm was selected as the abrasive. The abrasive was required to be angular, clean, dry, and free of oil.
[0057] All compressed air undergoes a cooling device and an oil-water separator during the injection process to ensure that the compressed air is dry, oil-free, and at a pressure of 0.7 MPa.
[0058] Maintain a distance of 100mm between the nozzle and the base metal surface;
[0059] The angle between the spraying direction and the normal to the base metal surface is controlled within 15 degrees.
[0060] After surface pretreatment, remove dust and debris with dry, oil-free compressed air. Do not touch the cleaned surface with your hands.
[0061] Step 2: Plasma spray Zn-Al alloy onto the substrate surface after Step 1, and then plasma spray Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials in a ratio of 2:3:2:1:2 onto the metal layer to obtain a substrate with a metal-ceramic base layer.
[0062] Step 3: Using ethyl acetate as a solvent, prepare a mixed solution of SEBS (hydrogenated styrene-butadiene block copolymer), MA-SEBS (maleic anhydride-modified SEBS), and macromolecular coupling agent (C8H22O3N2Si) with a concentration ratio of 1:1:2. Then, use a booster pump to increase the pressure of the coating to 160-280 kg / cm² on the substrate surface treated in Step 2. 2 Spraying a 60μm layer, the silanol groups on the macromolecular coupling agent organically combine with the -OH groups on the surface of the metal-ceramic base layer, and the epoxy groups and amino groups bond with the maleic anhydride-modified SEBS in the metal-ceramic base layer, so that SEBS grows on the surface of the metal-ceramic material, and an SEBS structure layer is obtained.
[0063] Step 4: Prepare an ethyl acetate solution containing the block polymer PS-b-PDMS-r-PVMS with a concentration of 10 mol / L. Mix the prepared ethyl acetate solution with FeCo / gelatin nanospheres that have adsorbed small molecules, and then coat the substrate surface treated in Step 3 with a thickness of 35 μm to complete the overall coating.
[0064] The specific spraying parameters are as follows: metal layer spraying parameters: working current 400, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.15L / min, alloy powder feeding rate 80g / min, and spraying thickness 150μm;
[0065] Ceramic layer spraying parameters: operating current 500, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.25L / min, alloy powder feeding rate 75g / min, spraying thickness 120μm.
[0066] The metal-ceramic base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate. The substrate is cleaned and sandblasted. Zn-Ni alloy is used as the metal layer material, and Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides are used as ceramic layer raw materials. The metal layer material is arc-sprayed onto the substrate surface and then the ceramic layer raw materials are arc-sprayed to obtain a double base layer of metal and ceramic layers.
[0067] The Zn-Ni balance is 20%~35%, and the mass ratio of Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides is 2:3:2:1:2.
[0068] Example 3:
[0069] A spraying process for a marine antifouling and anticorrosion coating:
[0070] Step 1: Based on the substrate, the substrate is cleaned and sandblasted; the surface cleanliness after treatment reaches Sa3 and the roughness reaches Rz25-100μm.
[0071] Sandblasting process parameters
[0072] Cast iron sand with a particle size of 1mm was selected as the abrasive. The abrasive was required to be angular, clean, dry, and free of oil.
[0073] All compressed air undergoes a cooling device and an oil-water separator during the injection process to ensure that the compressed air is dry, oil-free, and at a pressure of 0.7 MPa.
[0074] Maintain a distance of 200mm between the nozzle and the base metal surface;
[0075] The angle between the spraying direction and the normal to the base metal surface is controlled within 15 degrees.
[0076] After surface pretreatment, remove dust and debris with dry, oil-free compressed air. Do not touch the cleaned surface with your hands.
[0077] Step 2: Plasma spray Zn-Al alloy onto the substrate surface after Step 1, and then plasma spray Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials in a ratio of 2:3:2:1:2 onto the metal layer to obtain a substrate with a metal-ceramic base layer.
[0078] Step 3: Using ethyl acetate as a solvent, prepare a mixed solution of SEBS (hydrogenated styrene-butadiene block copolymer), MA-SEBS (maleic anhydride-modified SEBS), and macromolecular coupling agent (C8H22O3N2Si) with a concentration ratio of 1:1:2. Then, use a booster pump to increase the pressure of the coating to 160-280 kg / cm² on the substrate surface treated in Step 2. 2 ) Spraying 50μm, the silanol groups on the macromolecular coupling agent organically combine with the -OH on the surface of the metal-ceramic base layer, and the epoxy groups and amino groups bond with the maleic anhydride-modified SEBS in the metal-ceramic base layer, so that SEBS grows on the surface of the metal-ceramic material and obtains the SEBS structure layer.
[0079] Step 4: Prepare an ethyl acetate solution containing the block polymer PS-b-PDMS-r-PVMS with a concentration of 10 mol / L. Mix the prepared ethyl acetate solution with FeCo / gelatin nanospheres that have adsorbed small molecules, and then coat the substrate surface treated in Step 3 with a thickness of 30 μm to complete the overall coating.
[0080] The specific spraying parameters are as follows: metal layer spraying parameters: working current 400, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.15L / min, alloy powder feeding rate 80g / min, and spraying thickness 150μm;
[0081] Ceramic layer spraying parameters: operating current 500, Ar gas flow rate 0.55L / min, N2 gas flow rate 0.3L / min, H2 gas flow rate 0.25L / min, alloy powder feeding rate 75g / min, spraying thickness 120μm.
[0082] The metal-ceramic base layer uses zinc-aluminum-ceramic composite alloy wire as the metal substrate. The substrate is cleaned and sandblasted. Zn-Ni alloy is used as the metal layer material, and Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides are used as ceramic layer raw materials. The metal layer material is arc-sprayed onto the substrate surface and then the ceramic layer raw materials are arc-sprayed to obtain a double base layer of metal and ceramic layers.
[0083] The Zn-Ni balance is 20%–35%, and the mass ratio of Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides is 2:3:2:1:2.
[0084] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations within the meaning and scope of equivalents of the potential claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0085] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A marine antifouling and anticorrosion coating, characterized in that: It includes a metal-ceramic base layer, an SEBS structural layer, and a PS-b-PDMS-r-PVMS / MNPs@Laf active layer; Metal-ceramic base layer: Using Zn-Al alloy as the metal layer material and Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials, the metal layer material is plasma sprayed onto the surface of a substrate and then the ceramic layer raw materials are plasma sprayed to obtain the metal-ceramic base layer. SEBS structural layer: Hydrogenated styrene-butadiene block copolymer, maleic anhydride-modified SEBS, and macromolecular coupling agent C8H22O3N2Si are coated on the surface of the metal-ceramic base layer. The -OH groups on the surface of the metal-ceramic base layer are organically combined with the silanol groups at one end of the macromolecular coupling agent, and the epoxy groups and amino groups at the other end of the macromolecular coupling agent are bonded to the maleic anhydride-modified SEBS in the metal-ceramic base layer to obtain the SEBS structural layer. PS-b-PDMS-r-PVMS / MNPs@Laf active layer: The block polymer PS-b-PDMS-r-PVMS was dissolved in ethyl acetate and uniformly mixed with FeCo / gelatin nanospheres adsorbed with small molecules. This mixture was then coated onto the SEBS structural layer to obtain the PS-b-PDMS-r-PVMS / MNPs@Laf active layer. An antifouling and anticorrosion coating is obtained by setting the SEBS structural layer on the metal-ceramic base layer and setting the PS-b-PDMS-r-PVMS / MNPs@Laf active layer on the basis of the SEBS structural layer.
2. The marine antifouling and anticorrosion coating according to claim 1, characterized in that: The mass ratio of Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides is 2:3:2:1:
2.
3. The spraying process for a marine antifouling and anticorrosion coating according to claim 1, characterized in that: Includes the following steps: Step 1: Based on the metal substrate, the metal substrate is cleaned and sandblasted; the surface cleanliness after treatment reaches Sa3, and the roughness reaches Rz25~100μm; Step 2: Plasma spray Zn-Al alloy onto the surface of the metal substrate after Step 1, and then plasma spray Cr2O3, Al2O3, TiO2, SiO2 and rare earth oxides as ceramic layer raw materials in a ratio of 2:3:2:1:2 onto the metal layer to obtain a substrate with a metal-ceramic base layer. Step 3: Using ethyl acetate as a solvent, prepare a mixed solution of hydrogenated styrene-butadiene block copolymer, maleic anhydride-modified SEBS, and macromolecular coupling agent C8H22O3N2Si with a concentration ratio of 1:1:
2. Then, use a booster pump to increase the pressure of the coating to 160-280 kg / cm² and spray it to a thickness of 50 μm on the surface of the metal-ceramic base layer. The silanol groups on the macromolecular coupling agent are organically combined with the -OH groups on the surface of the metal-ceramic base layer, and the epoxy groups and amino groups are bonded to the maleic anhydride-modified SEBS in the metal-ceramic base layer, so that SEBS grows on the surface of the metal-ceramic material to obtain the SEBS structure layer. Step 4: Prepare an ethyl acetate solution containing the block polymer PS-b-PDMS-r-PVMS with a concentration of 10 mol / L. Mix the prepared ethyl acetate solution with FeCo / gelatin nanospheres that have adsorbed small molecules, and then coat the substrate surface treated in Step 3 with a thickness of 30 μm to complete the overall coating.
4. The spraying process for a marine antifouling and anticorrosion coating according to claim 3, characterized in that: The sandblasting process is as follows: Cast iron sand is selected as the abrasive, with a particle size of 0.5mm to 1.5mm. The abrasive must be angular, clean, dry, and free of oil. All compressed air undergoes a cooling device and an oil-water separator during the injection process to ensure that the compressed air is dry, oil-free, and at a pressure of 0.7 MPa. Maintain a distance of 100mm to 300mm between the nozzle and the base metal surface; The angle between the spraying direction and the normal to the base metal surface is controlled within the range of 15° to 30°. After surface pretreatment, remove dust and debris with dry, oil-free compressed air. Do not touch the cleaned surface with your hands.
Citation Information
Patent Citations
Composite coating with friction-decreasing function and biological-foul and seawater resistances and its production
CN101074331A
Thermoplastic elastomer sealing strip material and preparation method thereof
CN102604312A